FDTD method for the analysis of the EM field from a moving source - Shafrida, Sahrani; Tatsuya, Akata; Michiko, Kuroda (IEEE, 2013)
A numerical technique for the analysis of the EM field by a moving source or a moving body can be significantly important for the realization of new optical/nanotechnology devices. We have previously proposed the Overset Grid Generation method coupled with FDTD method for the analysis of the EM field with moving boundaries considering Doppler Effect. By overlapping one moving sub-mesh on a static main mesh, each mesh is calculated alternately by using interpolation technique. For higher velocity value, Lorentz transformation is applied to the FDTD method. In this paper, this technique is proposed for solving the EM field when the input source is moving. As a bench mark, the received wave at the observation point is calculated when the source moves for x-direction in free space intersect at right angle by the dielectric object. The numerical results are compared with the stationary case and the moving case.